2011
DOI: 10.1080/13691058.2011.583682
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning and deciding PMTCT-adherence during pregnancy among women living with HIV in Kenya

Abstract: This study explores type identities among rural and urban slum women on antiretroviral therapies who become pregnant. Narrative structuring was chosen to develop type narratives that illustrate how rural and urban women handle their HIV-infection and how they reason and decide about PMTCT-adherence during pregnancy and childbirth. Women in rural areas described their lives as 'secure and family controlled'. This gave the women security and predictability in life, but also meant that it was difficult to keep se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 15 publications
6
40
0
Order By: Relevance
“…Poor adherence among pregnant women may relate to challenges around partner disclosure [44]. In a recent systematic review of PMTCT, partner disclosure was associated with poor PMTCT uptake in a majority of both quantitative (6 of 9) and qualitative (17 of 24) studies [45].…”
Section: Discussionmentioning
confidence: 99%
“…Poor adherence among pregnant women may relate to challenges around partner disclosure [44]. In a recent systematic review of PMTCT, partner disclosure was associated with poor PMTCT uptake in a majority of both quantitative (6 of 9) and qualitative (17 of 24) studies [45].…”
Section: Discussionmentioning
confidence: 99%
“…Often, HIV-positive women’s attitude, perceived norms, and personal agency are cited as ways to understand and address PMTCT adherence (Awiti Ujiji et al, 2011; Nyasulu & Naysulu, 2011; Varga & Brookes, 2008). The problem with examining PMTCT adherence using only intrapersonal constructs is that the sole responsibility to prevent MTCT is thereby placed on the HIV-positive mother, without taking into account the context in which these health behaviors occur and the large gender inequities that persist both within society and sexual relationships (Campbell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies in sub-Saharan Africa have suggested that pregnant women avoid health clinics if they fear HIV testing or unwanted HIV status disclosure [13]–[15]. Indeed, stigma and discrimination have been revealed as among the most important barriers to pregnant women's acceptance of HIV testing during antenatal care [16][18], their initial participation in programs for PMTCT [19],[20], and their retention and adherence in these programs [21][23].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies suggest that for pregnant women in high HIV-prevalence settings, HIV-related stigma—especially from a woman's male partner—may be a key factor causing women to avoid antenatal clinics (ANC) and childbirth in health facilities [33],[34]. Maternity services have become prime locations for HIV testing and provision of PMTCT interventions in Kenya and many other countries.…”
Section: Introductionmentioning
confidence: 99%